1993
DOI: 10.1007/bf01474681
|View full text |Cite
|
Sign up to set email alerts
|

Effect of beta-N-oxalylamino-l-alanine on cerebellar cGMP level in vivo

Abstract: Beta-N-oxalylamino-L-alanine (BOAA), a non-protein amino acid present in the seeds of Lathyrus Sativus (LS), is one of several neuroactive glutamate analogs reported to stimulate excitatory receptors and, in high concentrations, cause neuronal degeneration. In the present study, the in vivo acute effects of synthetic BOAA and LS seed extract were investigated on rat cerebellar cyclic GMP following intraperitoneal (10-100 mg/kg) or oral (100 mg/kg) administration of subconvulsive doses of toxin. Furthermore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…I. Poma (Institute of Agronomy, University of Palermo, Italy). The BOAA content in the LS seeds was estimated by HPLC analysis and ranged between 1 and 2 mg/g seeds (La Bella et al, 1993a). Conversely, in the CA seeds the content of neurotoxin, assayed by the same method, was negligible.…”
Section: Seedsmentioning
confidence: 99%
See 1 more Smart Citation
“…I. Poma (Institute of Agronomy, University of Palermo, Italy). The BOAA content in the LS seeds was estimated by HPLC analysis and ranged between 1 and 2 mg/g seeds (La Bella et al, 1993a). Conversely, in the CA seeds the content of neurotoxin, assayed by the same method, was negligible.…”
Section: Seedsmentioning
confidence: 99%
“…Recently, we have demonstrated that BOAA, either synthetic or extracted from LS seeds, when administered at subconvulsive doses to rats (50-100 mg/kg) is able to specifically increase cerebellar cyclic GMP levels (La Bella et al, 1993a) as well as to induce a down-regulation of non-NMDA glutamate receptors in the frontal cortex (La Bella et al, 1993b), thereby providing further support of a neurotoxin-mediated activation of glutamatergic synapse in vivo. However, neither neurological deficits nor behavioral abnormalities could be observed in the animals treated.…”
Section: Introductionmentioning
confidence: 96%
“…17,18 Oral administration of nonconvulsant doses of β-L-ODAP to rats increases the cerebellar cyclic guanosine monophosphate (cGMP) level and induces downregulation of non-NMDA glutamate receptors in the frontal cortex. 19,20 However, little is known about the cellular mechanism of β-L-ODAP excitotoxicity on glutamate and other related neuroreceptors on systemic administration of lathyrus pulse. A recent study has demonstrated neurobehavioural changes in rats, in terms of increased open field activity following long-term dietary feeding of lathyrus pulse, 21 but further investigations are needed to elucidate the in vivo neurotoxicity of orally fed lathyrus pulse at different doses that can be achieved to the human population.…”
Section: Introductionmentioning
confidence: 99%